B cells are not drivers of stromal cell activation during acute CNS infection - Brendan T. Boylan; Mihyun Hwang; Elyse Brozost; Hyunsuk Oh; Alexei V. Tumanov; Antoine Louveau; Cornelia C. Bergmann (Journal of Neuroinflammation)
Abstract Background CNS stromal cells, especially fibroblasts and endothelial cells, support leukocyte accumulation through upregulation of adhesion molecules and lymphoid chemokines. While chronically activated fibroblast networks can drive pathogenic immune cell aggregates known as tertiary lymphoid structures (TLS), early stromal cell activation during CNS infection can support anti-viral T cells. However, the cell types and factors driving early stromal cell activation is poorly explored. Aims A neurotropic murine coronavirus (mCoV) infection model was used to better characterize signals that promote fibroblast networks supporting accumulation of antiviral lymphocytes. Based on the early appearance of IgD+ B cells with unknown functions during several CNS infections, we probed their potential to activate stromal cells through lymphotoxin β (LTβ), a molecule critical in maintaining fibroblast-networks in lymphoid tissues as well as promoting TLS in autoimmunity and cancers. Results Kinetic analysis of stromal cell activation in olfactory bulbs and brains revealed that upregulation of adhesion molecules and lymphoid chemokines Ccl19, Ccl21 and Cxcl13 closely tracked viral replication. Immunohistochemistry revealed that upregulation of the fibroblast marker podoplanin (PDPN) at meningeal and perivascular sites mirrored kinetics of RNA expression. Moreover, both B cells and T cells colocalized to areas of PDPN reactivity, supporting a potential role in regulating stromal cell activation. However, specific depletion of LTβ from B cells using Mb1-creERT2 x Ltβfl/fl mice had no effect on T or B cell recruitment or viral replication. B cell depletion by anti-CD20 antibody also had no adverse effects. Surprisingly, LTβR agonism reduced viral control and parenchymal T cell localization despite increasing stromal cell lymphoid chemokines and PDPN. Additional assessment of direct stromal cell activation by the viral RNA mimic poly I:C showed induction of Pdpn and Ccl19 preceding Ltb. Conclusions Neither B cell-derived LTβ or B cells are primary drivers of stromal cell activation networks in the CNS following mCoV infection. Although supplementary agonist mediated LTβR engagement confirmed a role for LTβ in enhancing PDPN and lymphoid chemokine expression, it impeded T cell migration to the CNS parenchyma and viral control. Our data overall indicate that stromal cells can integrate LTβR signals to tune their activation, but that LTβ is not necessarily essential and can even dysregulate protective antiviral T cell functions.